Hedge Accounting and Market Value of Quoted Manufacturing Firms in Nigeria: Panel Data Evidence - Captain Briggs, Alasin (International Journal of Accounting & Finance Review, 2018)
In a developing economy such as Nigeria, the business environment is characterized with risk that affects the operational efficiency and the performance of quoted firms. There is needed to make policies that will hedge against risk in the operating environment. This study examined the effect of hedge accounting on the market value of quoted oil and gas firms. A sample of 10 oil and gas firms was selected based on data quality and availability to address the requirements of the variables in the regression model. The study modeled market value as linear function of cash flow hedging, investment hedging and fair value hedging. Cross sectional data was sources from financial statement of the selected firms from 2011 to 2016. From the panel data result, (Fixed Effect Model) the study found that cash flow hedging have positive and significant relationship with market value while fair value hedging and investment hedging have positive but not significant relationship with market value of the quoted oil and gas firms.   We therefore recommend that hedge accounting policies should be properly integrated to the operational objectives of the firms.